2020
DOI: 10.1155/2020/4898123
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis of Step-Stress Accelerated Life Test with Random Group Effects under Weibull Distribution

Abstract: Step-stress accelerating life test (SSALT), aiming to predict the failure behavior under use condition by the data collected from elevated test setting, is implemented to specimen with time-varying stress levels. Typical testing protocols in SSALT, such as subsampling, cannot guarantee complete randomization and thus result in correlated observations among groups. To consider the random effects from the group-to-group variation, we build a nonlinear mixed effect model (NLMM) with the assumption of Weibull dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The posterior density function in (14) for the two parameters ψ and ζ can be formed by the multiplication of Equations (6) with (11) and making some simplification, and its final form is as below:…”
Section: Bayes Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior density function in (14) for the two parameters ψ and ζ can be formed by the multiplication of Equations (6) with (11) and making some simplification, and its final form is as below:…”
Section: Bayes Estimationmentioning
confidence: 99%
“…The importance of the Lindley distribution in this paper is that it provides more fit than its traditional competitor, the two-parameter Weibull distribution, as we checked for the p-value for both distributions for fitting the real data application and found that the Lindley distribution has p-value greater than 0.05 for both levels of stress in the experiment, while in case of the Weibull distribution it makes a poor-fitting for the real data set because the p-value of the first level of acceleration is less than 0.05, while it provides good fitting for the second level, so we can deduce that the Lindley distribution makes better fitting than the Weibull distribution for both levels of experiment so we can use it instead of the Weibull distribution by fitting the two levels of the Lindley distribution which has a merit over the two parameters Weibull distribution in fitting this kind of experiment. For more information about the reliability of engineering data, please see references [12][13][14].…”
Section: Comparison With Competitive Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdelmonem and Jaheen (2017) considered a SSALT study assuming that the lifetime follows a generalized exponential distribution based on Type-II censored data and applying MLE and Bayesian approaches. Samanta et al (2018) provide the order-restricted Bayesian inference of a simple step-stress test and more recently, Wang (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sha and Pan (2014) presented a Bayesian approach for the Weibull proportional hazard model used in SSALT. Wang (2020) built a non-linear mixed model with the assumption of the Weibull distribution for lifetime data analysis from SSALT to consider the random effects from the group-to-group variation.…”
mentioning
confidence: 99%